Penerapan Hierarchical Finite State Machine untuk Pengambilan Keputusan Non-Player Character (Studi Kasus: Gim Hack and Slash) - Ahmad Fadli Naharu; Eriq Muhammad Adams Jonemaro; Muhammad Aminul Akbar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Hack and slash is a genre of a video game that a player is playing as a character that beats enemies using melee weapon. The enemies in this kind of game are non-player characters. Which mean those characters are controlled by machine instead of human. Because of that reason, developing NPCs in a video game like hack and slah is important. We've implemented three NPCs in this reaserch, they are called NPC1, NPC2 and NPC3. They are designed in states and transitions using Hirarchical Finite State Machine and implemented in Unity game engine. Those NPCs are tested using Test Flow Diagram and Frame Per Second Test. The result of TFD shown that NPCs are working normally as expected in genereted flows. And the last for FPS test shown that on the system spesification, NPC1 could run the game up to 250 NPCs at 60 FPS. For NPC2 and NPC3 could run the game up to 200 NPCs at 60 FPS.